Cytosolic malate dehydrogenase 4 modulates cellular energetics and storage reserve accumulation in maize endosperm. Issue 12 (14th June 2020) - Chen, Yongqiang; Fu, Zhiyuan; Zhang, Hui; Tian, Runmiao; Yang, Huili; Sun, Canran; Wang, Lulin; Zhang, Wen; Guo, Zhanyong; Zhang, Xuehai; Tang, Jihua
Abstract: Cytosolic malate dehydrogenase (MDH) is a key enzyme that regulates the interconversion between malate and oxaloacetate (OAA). However, its role in modulating storage compound accumulation in maize endosperm is largely unknown. Here, we characterized a novel naturally occurring maize mdh4‐1 mutant, which produces small, opaque kernels and exhibits reduced starch but enhanced lysine content. Map‐based cloning, functional complementation and allelism analyses identified ZmMdh4 as the causal gene. Enzymatic assays demonstrated that ZmMDH4 predominantly catalyses the conversion from OAA to malate. In comparison, the activity of the mutant enzyme, which lacks one glutamic acid (Glu), was completed abolished, demonstrating that the Glu residue was essential for ZmMDH4 function. Knocking down ZmMdh4 in vivo led to a substantial metabolic shift towards glycolysis and a dramatic disruption in the activity of the mitochondrial complex I, which was correlated with transcriptomic alterations. Taken together, these results demonstrate that ZmMdh4 regulates the balance between mitochondrial respiration and glycolysis, ATP production and endosperm development, through a yet unknown feedback regulatory mechanism in mitochondria.